ANALISIS PENGARUH JUB, INFLASI, KURS, DAN IHSG TERHADAP KINERJA REKSA DANA SYARIAH DI INDONESIA PADA TAHUN 2015 HINGGA 2020 - Iswan Noor; Ayunata, Nabila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the factors that influence the performance of Islamic Mutual Funds in Indonesia from 2015 to 2020. The research data were obtained from official publications of the Financial Services Authority and the official website of state data providers. This study uses 5 variables consisting of 1 dependent variable and 4 independent variables. Sharia Mutual Funds performance variable is measured by Net Asset Value (NAV) as the dependent variable. Money Supply, Inflation, Exchange Rate, and Indonesia Composite Index variables as independent variables. This study used the VAR/VECM method with Stata14 software. The results of this study indicate that in the short term, the Indonesia Composite Index variable and the NAV variable itself have a negative and significant effect. Meanwhile, in the long run, only the Indonesia Composite Index variable affects NAV. Meanwhile, the variables of Money Supply, Inflation, and Exchange Rates do not significantly influence the performance of Islamic Mutual Funds in Indonesia from 2015 to 2020.